INFORMATION SYSTEM FOR MONITORING COMMUNITY PARTICIPANT PROGRAM SERVICES IN THE COVID-19 PANDEMIC ERA - Bangun Wijayanto; Yogiek Indra Kurniawan; Teguh Cahyono; Indra Permana Jati (Jurnal Teknik Informatika (Jutif), 2022)
Community Participant Program Services (In Indonesia: Kuliah Kerja Nyata/KKN) is an activity that must be carried out by final year students in Indonesia. Community Participant Program Services are intended so that students can apply the knowledge gained in lectures to people's lives. The Covid-19 pandemic made all available resources mobilized to be able to cope with the pandemic that occurred, Community Participant Program Services were directed by the Indonesian Ministry of Education and Culture to be able to help the situation by making Community Participant Program Services in the form of Covid 19 volunteers. Indonesia is an archipelagic country consisting of 33 provinces and more than 17000 islands with diverse geographical contours and unattended telecommunication facilities in all locations requiring a volunteer monitoring system that is simple, effective, and easy to use. The system proposed in this research is based on telegram which has the advantage of ease and speed of development in adapting to changes in the rules that apply during the epidemic period. This research has contributed to monitoring the activities and health of the 2847 Covid-19 volunteers from Universitas Jenderal Soedirman who are scattered throughout Indonesia and facilitating decision.